ANALISIS FAKTOR-FAKTOR PRODUKTIVITAS TENAGA KERJA PADA PROYEK PEMBANGUNAN MENARA PUSAT KULINER DAN CENDRAMATA KOTA PALOPO - Muhammad Saleh; Sudarman Supardi; Watono (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
Productivity is an important factor for determining the success of a project, if employee work productivity always experiences a significant increase from time to time, the company will easily achieve the goals that have been set. The purpose of this study was to analyze the factors of labor productivity in the construction project of the culinary center tower and souvenirs in Palopo City. The variables studied include labor productivity as the dependent variable and compensation, knowledge, skills, abilities, attitudes, behavior as independent variables. The method used in the analysis process is the Prerequisite Analysis Test and the Multiple Linear Regression Hypothesis Test. Results of this Research. Factors that have a significant positive effect on Workforce Productivity include: Compensation, Skills, Capability, Behavior, While factors that have a not significant positive effect are Knowledge and Attitudes. Of the several factors that have a significant positive effect, there is a variable that has the most influence with a value below 0.05, namely the behavioral factor variable.